Existence of Solutions of α∈(2,3] Order Fractional Three-Point Boundary Value Problems with Integral Conditions - N. I. Mahmudov; S. Unul (Abstract and Applied Analysis)
Existence and uniqueness of solutions for α∈(2,3] order fractional differential equations with three-point fractional boundary and integral conditions involving the nonlinearity depending on the fractional derivatives of the unknown function are discussed. The results are obtained by using fixed point theorems. Two examples are given to illustrate the results.